Right Coronary artery Myocardial Bridging - Ather Mehmood; Rizwan Uppal; Hassan Saleem; Attiya Hameed Khan (Pakistan Journal of Medical & Health Sciences, 2024)
Myocardial bridge (MB) is a non-atherosclerotic anatomical anomaly of coronary arteries, giving upward thrust to ischemic events. The chief coronary arteries run along the grooves and the heart epicardia surface1. Within such normal distribution, in some topics a coronary vessel deepens into the myocardial wall for a variable period and runs wound through muscle bundles. This is known as the myocardial bridge. The coronary arteries may also run into the myocardium for variable distance and then become apparent on the coronary heart surface. When a muscle opposes the intramyocardial phase of the epicardia coronary artery it is referred to as a myocardial bridge whereas coronary artery running within the myocardium is called a tunneled artery3. The myocardial bridges have been named with regard to clinical literature and the most commonly affected artery is the anterior interventricular branch of the left coronary artery4. Coronary MDCT angiography has been used in the assessment of coronary anomalies among patients and has been described as a wholly non-invasive diagnostic technique.